2004
DOI: 10.1590/s0102-09352004000600007
|View full text |Cite
|
Sign up to set email alerts
|

Ocorrência de Babesia sp em pequenos roedores no Brasil

Abstract: RESUMOFoi analisada a ocorrência de babesiose em pequenos roedores nos municípios de Silva Jardim e Nova lguaçu, Estado do Rio de Janeiro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 12 publications
0
3
0
1
Order By: Relevance
“…The prevalence of infection was 27,3% in two species: Oligoryzomys nigripes and Rattus norvergicus. The other captured species were: Nectomys squamipes, Oryzomys angoya, Holochilus brasiliensis and Akodon cursor (Gazeta et al, 2004).…”
Section: Specie Area I-itatiaiamentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of infection was 27,3% in two species: Oligoryzomys nigripes and Rattus norvergicus. The other captured species were: Nectomys squamipes, Oryzomys angoya, Holochilus brasiliensis and Akodon cursor (Gazeta et al, 2004).…”
Section: Specie Area I-itatiaiamentioning
confidence: 99%
“…However, few studies have been done on hosts and reservoirs in Brazilian native species (Dall´olio et al, 2001;Gazeta et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies with Mycoplasma in rodents show a significant impact of infection by M. pulmonis, which interferes with interpreting the experimental results obtained with infected animals (Tedesco et al, 2011). Gazeta et al (2004) Shih et al (1997) that also reported the infection in rodents (Rattus coxinga) from rural zones of Taiwan, close to highly populated areas, calling the attention to the risk of human Babesiosis and alerting to the evident emergency of research in species with host potentials of parasites and their unknown vectors. Therefore, it is of fundamental importance to detect and identify these hemoparasites in the G. spixii due to the potential risk of introducing possible infected specimen of this species in zoos, urban areas and households, due to the transport, interaction, manipulation, import, and transfer of these animals (B. S. Lima et al, 2013).…”
Section: Blood Countmentioning
confidence: 99%
“…[12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33] . Estes dados foram agrupados, removidos os registros duplicados ou duvidosos, sendo consideradas as informações que continham a coordenada geográfica do ponto de coleta do respectivo espécime.…”
Section: Análise Multicritério De Decisão (Amd)unclassified